2019
DOI: 10.3390/ma12111814
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Chemistry and Antibacterial Properties of Cupriferous Hydroxyapatite

Abstract: Copper-doped hydroxyapatite (HA) of nominal composition Ca10(PO4)6[Cux(OH)2-2xOx] (0.0 ≤ x ≤ 0.8) was prepared by solid-state and wet chemical processing to explore the impact of the synthesis route and mode of crystal chemical incorporation of copper on the antibacterial efficacy against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) strains. Apatites prepared by solid-state reaction showed unit cell volume dilation from 527.17 Å3 for copper-free HA to 533.31 Å3 for material of the putative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Radovanovic et al (2014) [ 14 ], synthetized Cu-doped BCP powders (HAp/α-TCP), and the results indicated significant antibacterial activity after 24 h of incubation for the four tested microorganisms, MSSA , E. coli , P. aeruginosa and C. albicans, compared to undoped HAp/α-TCP. Recently, Bhattacharjee et al (2019) [ 15 ]. prepared Cu-doped hydroxyapatite.…”
Section: Introductionmentioning
confidence: 99%
“…Radovanovic et al (2014) [ 14 ], synthetized Cu-doped BCP powders (HAp/α-TCP), and the results indicated significant antibacterial activity after 24 h of incubation for the four tested microorganisms, MSSA , E. coli , P. aeruginosa and C. albicans, compared to undoped HAp/α-TCP. Recently, Bhattacharjee et al (2019) [ 15 ]. prepared Cu-doped hydroxyapatite.…”
Section: Introductionmentioning
confidence: 99%
“…The term “apatite” refers to a supergroup of minerals of general chemical formula [A I 4 A II 6 ]­[MO 4 ] 6 [X 2 ], where A 2+ is a larger cation such as Ca 2+ , within CaO 6 X and CaO 9 polyhedra, M is a smaller cation such as P (notionally P 5+ ), and X – an anion such as a halide or OH – . This supergroup includes a wide range of cation and anion substitutions, with variations in the symmetry resulting from possible cation ordering and changes to topology .…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the Ca/P ratio of all materials was close to human HA [ 40 ]. Furthermore, the Ca/P ratio of 1.67 is also widely used as a reference value for bone grafts, rendering it suitable for orthopedic, dental, and maxillofacial implants [ 41 , 42 ]. Thus, the Ca/Pa value of fabricated submicron BHA supported the potential of this material to be used for bone implants.…”
Section: Discussionmentioning
confidence: 99%